Helical Carbenium Ion-Based Organic Photoredox Catalyst: A Versatile and Sustainable Option in Red-Light-Induced Reactions - Mei, Liangyong; Gianetti, Thomas (Synlett, 2020)
The development of a sustainable catalytic system for red-light-induced photocatalysis is presented. The catalytic system consists of a helical carbenium ion-based organic photoredox catalyst (PC) that is capable of using low-energy red light (λmax = 640 nm) for both photooxidations and photoreductions. Its successful applications in the aerobic oxidative hydroxylation of arylboronic acids and in the oxidation of benzylic C(sp3)–H bonds (reductive quenching), as well as in dual transition-metal/organocatalyzed C–H arylations and intermolecular atom-transfer radical additions (oxidative quenching) provide further support for its role as a versatile and efficient organic PC.1 Introduction2 Red-Light-Induced Photocatalysis3 Properties of N,N′-Dipropyl-1,13-dimethoxyquinacridinium Tetrafluoroborate4 Two Proposed Representative Catalytic Cycles of [nPr-DMQA+][BF4–]5 Applications of [nPr-DMQA+][BF4–] in Red-Light-Induced Photocatalysis6 Conclusion
Keywords: photocatalysis; helical carbenium ions; organic photoredox catalyst; red-light-induced reactions; photooxidation; photoreduction